BEECLUST used for exploration tasks in Autonomous Underwater Vehicles. Issue 1 (2015) - Bodi, Michael; Möslinger, Christoph; Thenius, Ronald; Schmickl, Thomas
Abstract: Underwater exploration is still a difficult task these days. In this paper we suggest a swarm of Autonomous Underwater Vehicles (AUVs) for such tasks. These AUVs are controlled by BEECLUST which is a swarm control algorithm inspired by honeybee behaviour. A swarm controlled by BEECLUST shows very reliable aggregation behaviour in a global optimum. In a simulation experiment we show that BEECLUST is very well adaptable for AUV swarms. Furthermore we show that BEECLUST is not only capable of showing aggregation behaviour but also is a valid tool for underwater exploration tasks.